2015
DOI: 10.1097/j.pain.0000000000000104
|View full text |Cite
|
Sign up to set email alerts
|

Sensitization of nociceptive spinal neurons contributes to pain in a transgenic model of sickle cell disease

Abstract: Chronic pain is a major characteristic feature of sickle cell disease (SCD). The refractory nature of pain and the development of chronic pain syndromes in many patients with SCD suggest that central neural mechanisms contribute to pain in this disease. We used HbSS-BERK sickle mice, which show chronic features of pain similar to those observed in SCD, and determined whether sensitization of nociceptive neurons in the spinal cord contributes to pain and hyperalgesia in SCD. Electrophysiological recordings of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
81
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 88 publications
(89 citation statements)
references
References 52 publications
5
81
1
2
Order By: Relevance
“…Indeed, second-order neurons in the dorsal horn of the spinal cord show constitutive nociceptor sensitization in electrophysiological recordings in the "ERK sickle mice [42]. Nociceptive neurons in the dorsal horn of sickle mice show increased excitability and an increased rate of spontaneous activity [42]. These electrophysiological responses are accompanied by higher response to mechanical stimuli and prolonged after-discharges following the mechanical stimulus, suggestive of central sensitization [42].…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, second-order neurons in the dorsal horn of the spinal cord show constitutive nociceptor sensitization in electrophysiological recordings in the "ERK sickle mice [42]. Nociceptive neurons in the dorsal horn of sickle mice show increased excitability and an increased rate of spontaneous activity [42]. These electrophysiological responses are accompanied by higher response to mechanical stimuli and prolonged after-discharges following the mechanical stimulus, suggestive of central sensitization [42].…”
Section: Figurementioning
confidence: 99%
“…Nociceptive neurons in the dorsal horn of sickle mice show increased excitability and an increased rate of spontaneous activity [42]. These electrophysiological responses are accompanied by higher response to mechanical stimuli and prolonged after-discharges following the mechanical stimulus, suggestive of central sensitization [42]. This sustained and continuous activation of spinal neurons may lead to increased release of neuropeptides and nociceptive mediators, which may be released into the periphery antidromically, in turn activating the peripheral nerve terminals without noxious insult.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…4 We recently observed that spinal nociceptive neurons are sensitized in sickle mice, suggestive of central sensitization. 5 Bidirectional signaling occurs between neurons and immunocompetent cells present in the CNS, including microglia, astrocytes and oligodendrocytes. 4 Activated microglia release reactive oxidative species (ROS), inflammatory cytokines, neurotrophic factors, and prostaglandins that excite nociceptive neurons and contribute to the persistence of chronic pain.…”
mentioning
confidence: 99%
“…Cataldo et al recently found an increase in spontaneous firing, receptor field size, and electrophysiological responses to low-threshold stimuli and mechanical stimuli in spinal dorsal horn neurons of HBSS-BERK SCD mice when compared to HBAA-BERK control mice. [53] The increases in several known signaling pathway components were observed including phosphorylated ERK, p38, TLR4, and IL-6. ERK phosphorylation has been shown to lead to decreased potassium currents associated with the Kv4.2 potassium channels translating into hyperexcitability of dorsal horn neurons.…”
Section: Potential Mechanisms Of Scd-associated Painmentioning
confidence: 99%